Urgensi Reformasi Kebijakan Tindak Pidana Pencucian Pencucian Uang Guna Implementasi Rupiah Digital - Firdaus, Sendy Pratama (AML/CFT Journal : The Journal Of Anti Money Laundering And Countering The Financing Of Terrorism, 2023)
This paper aims to examine the urgency of reformulating ML policies before the massive use of the Digital Rupiah. By combining doctrinal research methods and reform-oriented research, this paper finds that the current APUPPT policy is not sufficiently qualified in the stages towards massive use of Digital Rupiah. Based on these brief findings, this paper also offers novelty regarding the discussion between Digital Rupiah and money laundering, the source of which is taken from Bank Indonesia's white paper, so that it is different from other papers which only discuss the CBDC/Digital Rupiah concept in general and does not directly take from other sources. Bank Indonesia's white paper.